PENERAPAN ALOGRITMA LIPAT PADA STEGANOGRAFI YANG MEMANFAATKAN RMS ( RECORD MANAGEMENT SYSTEM ) DI J2ME - Wintolo, Hero; Retnowati, Nurcahyani Dewi; Fendriyanto, Prasetyo (Sekolah Tinggi Teknologi Adisutjipto, 2013)
The continued development of technology driven by the growing digital media facilities. A digital device in particular should pay attention to the level of security. Ease of sending messages in both text and image becomes very easy. However, one thing is important in the information, which can be performed using encryption steganography. In this thesis, steganography implemented by utilizing the mobile phone messaging facilities. The process of insertion into the text is converted into a binary image first, then take the final bit of the binary to insert text to be inserted. After the insertion process, the message to be sent by using the provider as the link destination address. The process of sending a message that has been tested on several telecommunication provider in Indonesia indicates the existence of different delivery success rate, but the message until it can not be opened unless the application has been made.